Construction of lift core / Siti Nurqamarina Zarqa Zakaria - Zakaria, Siti Nurqamarina Zarqa (2016)
BSB 351 - Practical Training refers to work experience that is relevant to professional development prior to graduation. One of the requirements for the students of Diploma in Building Surveying to complete the program is the students must complete at least 16 weeks of Practical Training. It started on 30th November 2015 and end on 30th March 2016. During the 4 months of practical training at Zikay Group Sdn. Bhd, Kampung Baru, Kuala Lumpur, have learned how theory and practical can be combined together in useful ways and how remarkable and enjoyable practical training could be. There are many type of maintenance and construction work have done while in Kembang Serantau team in Mercu Zikay. A part of this, renovation works also give a new and different knowledge about construction works. This high rise building in Mercu Zikay, have parking lot from level 1 until level 12 and hotels and apartments until level 40. At the roof top of the building, there are helipad provided. Objectives that can be achieve are such as to adapt to the dynamic working atmosphere and for apply the academic knowledge in managing workplace challenges. Next, it is also for apply the experience gained in the practical training for future learning in the university. With a lot of experiences, construction of elevator core has been chosen as case study for this report as it is also a part from study on last semester 4 in Building Services. Through practical training, trainee has gain an exposure to systematic work condition an environment that is conductive coupled with friendly staff that are always there to help. Hoping all of knowledge that has been gained can be use and help in future.